The Effect Of Brand Ambassador, Brand Trust And Brand Image On Purchase Decision On Beauty Product - Amelia Rizky; Rojuaniah Rojuaniah; Abdul Haeba Ramli; Zianneil T. Gecolea (Jurnal Ilmiah Manajemen Kesatuan, 2025)
This study aims to determine: the influence of brand ambassador, brand trust and brand image on purchase decision. This study uses a quantitative approach and primary data as a data source obtained from a questionnaire. The population of this study is people who know and have bought beauty products. The sample taken was 130 respondents using purposive sampling technique. The method of collecting data by distributing questionnaires using google form, in this study using a Likert scale with a scale of 1-4. This study uses multiple linear regression analysis with the influence of three independent variables and one dependent variable. Based on the results of the research that has been conducted, it shows that brand ambassador have a positive and significant effect on purchase decision, brand trust has a positive and significant effect on purchase decision, and brand image has a positive and significant effect on purchase decision. Brand ambassador, brand trust and brand image together have an effect on purchase decision. This research is expected to provide important insights for marketers in designing effective marketing strategies for beauty products, especially in choosing brand ambassador and building brand trust and positive brand image. Keywords: Brand Ambassador, Brand Trust, Brand Image, Purchase Decision